Defect-induced anisotropic surface reactivity and ion transfer processes of anatase nanoparticles. (September 2020) - Lee, M.-S.; Han, K.S.; Lee, J.; Shin, Y.; Kaspar, T.C.; Chen, Y.; Engelhard, M.H.; Mueller, K.T.; Murugesan, V.
Abstract: Surface reactivity and ion transfer processes of anatase TiO2 nanocrystals were studied using lithium bis(trifluoromethylsulfone)imide (LiTFSI) as a probing molecule. Analysis of synthesized anatase TiO2 by electron microscopy reveals aggregated nanoparticles (average size ~8 nm) with significant defects (holes and cracks). With the introduction of LiTFSI salt, the Li + -adsorption propensity towards the surface along the anatase (100) step edge plane is evident in both x-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) analysis. Ab initio molecular dynamics (AIMD) analysis corroborates the site-preferential interaction of Li + cations with oxygen vacancies and the thermodynamically favorable transport through the (100) step edge plane. Using 7 Li nuclear magnetic resonance (NMR) chemical shift and relaxometry measurements, the presence of Li + cations near the interface between TiO2 and the bulk LiTFSI phase was identified, and subsequent diffusion properties were analyzed. The lower activation energy derived from NMR analysis reveals enhanced mobility of Li + cations along the surface, in good agreement with AIMD calculations. On the other hand, the TFSI – anion interaction with defect sites leads to CF3 bond dissociation and subsequent generation of carbonyl fluoride-type species. The multimodal spectroscopic analysis including NMR, electron paramagnetic resonance (EPR), and x-ray photoelectron spectroscopy (XPS) confirms the decomposition of TFSI – anions near the anatase surface. The reaction mechanism and electronic structure of interfacial constituents were simulated using AIMD calculations. Overall, this work demonstrates the role of defects at the anatase nanoparticle surface on charge transfer and interfacial reaction processes. Graphical abstract: Image 1 Highlights: Surface reactivity and Li + transfer processes of anatase nanoparticles were studied using LiTFSI as a probing molecule. The Li + -adsorption propensity towards surface along the anatase (100) step edge plane is observed. The TFSI – anion interaction with surface defect sites leads to CF3 bond dissociation and radical transient species. The roles of surface defects on charge transfer and interfacial reaction process were analyzed.